2016
DOI: 10.5216/rpt.v45i3.43503
|View full text |Cite
|
Sign up to set email alerts
|

EPIDEMIOLOGIA DO VÍRUS DO DENGUE EM SÃO LUÍS, MARANHÃO, NO PERÍODO DE 2002 a 2012

Abstract: O presente estudo teve por objetivo relacionar a incidência do dengue com variáveis demográficas, temporais e meteorológicas, a fim de identificar as áreas com as mais elevadas incidências e determinar os sorotipos mais prevalentes, no período de 2002 a2012, no Município de São Luís, MA. Os dados foram extraídos dos boletins dos casos de dengue até então notificados, disponíveis na Secretaria Municipal de Saúde e Vigilância Epidemiológica e Sanitária do Município de São Luís, MA. Foi calculada estatística desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
2
1
2
Order By: Relevance
“…These climatic correlations were not statistically significant (P > 0.05). Some studies carried out in northeastern, southeastern and northern Brazil and abroad 16,18,19,20 have shown correlations contrary to those of the present study, given that they reported associations between climatic factors and the incidence of dengue. On the other hand, some other studies 28,29 have confirmed the lack of correlation of climatic factors with the incidence of dengue.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These climatic correlations were not statistically significant (P > 0.05). Some studies carried out in northeastern, southeastern and northern Brazil and abroad 16,18,19,20 have shown correlations contrary to those of the present study, given that they reported associations between climatic factors and the incidence of dengue. On the other hand, some other studies 28,29 have confirmed the lack of correlation of climatic factors with the incidence of dengue.…”
Section: Discussioncontrasting
confidence: 99%
“…18 In São Luis, state of Maranhão, a study covering 2002 to 2012 that included meteorological variables showed that the incidence of dengue fluctuated according to climatic periods, such that greater numbers of dengue cases occurred during the rainy season and at times of higher temperatures. 19 Another study carried out in northeastern Brazil in Maceió, state of Alagoas, covering 2010 to 2016, evaluated the correlation of meteorological parameters with the incidence of dengue. It showed that precipitation and humidity influenced the epidemiology of dengue.…”
Section: Discussionmentioning
confidence: 99%
“…A maior incidência da doença em adultos jovens, encontrada nesta pesquisa, corrobora com estudos realizados na cidade de Fortaleza (OLIVEIRA; ARAÚJO; CAVALCANTI, 2018) e São Luís (Carvalho et al, 2016). Outros autores como Pereira et al (2020) e Menezes et al (2021) também tiveram resultados semelhantes aos deste estudo.…”
Section: Resultsunclassified
“…Studies of the genetic variability of Ae. aegypti populations are extremely important for the Mid-North region of Brazil, where a large proportion of the municipalities are at risk of infestation by this vector and are thus faced with the potential spread of the dengue, chikungunya, and zika arboviruses [ 10 , 18 , 19 , 20 , 21 , 22 ]. In two previous studies in Maranhão, one of the Brazilian states that make up the Mid-North region, Fraga et al [ 23 ] and Sousa et al [ 24 ] found high levels of intra-population genetic differentiation in Ae.…”
Section: Introductionmentioning
confidence: 99%